2022
DOI: 10.1177/00219983211072955
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stress concentration sensitivity of SiCp/Al composite with network architecture

Abstract: For network architecture design, stress concentration sensitivity caused by particle shape may change, which is rarely studied. Here, the particle shape dependent stress concentration and its effect on the deformation, fracture and mechanical properties were investigated. Three particle shapes including hexahedron, twenty-six face polyhedron and sphere were utilized to generate different stress distribution states in the matrix. A numerical composite model showing network architecture (like grain boundary) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…18 As a result, the lack of wear resistance of the component results in failure and significant damage, depreciating the composite. 19,20 Using hard particles that are evenly distributed in the matrix, which increases wear resistance, is one of the typical methods for preventing wear in Al-MMCs. 18,19,21,22…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 As a result, the lack of wear resistance of the component results in failure and significant damage, depreciating the composite. 19,20 Using hard particles that are evenly distributed in the matrix, which increases wear resistance, is one of the typical methods for preventing wear in Al-MMCs. 18,19,21,22…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Using hard particles that are evenly distributed in the matrix, which increases wear resistance, is one of the typical methods for preventing wear in Al-MMCs. 18,19,21,22…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2022, the impact of particle geometry in the mechanical properties was numerical investigated, they used three different types of particle shapes. They found that the sphere particles reinforcing composite had improved the mechanical properties of composite materials [5].…”
Section: Introductionmentioning
confidence: 99%